Plain pottery traditions of the eastern Mediterranean and Near East production, use, and social significance - Glatz, Claudia 1979- (Publications of the Institute of Archaeology, University College London, 2016)
"The evolution and proliferation of plain and predominantly wheel-made pottery presents a characteristic feature of the societies of the Near East and Eastern Mediterranean since the fourth millennium B.C. This plain pottery has received little detailed archaeological attention in comparison to aesthetically more pleasing and chronologically sensitive decorated traditions. Yet, their simplicity and standardization suggest they are products of craft specialists, the result of high-volume production, and therefore important in understanding the social systems in early complex societies. This volume -reevaluates the role and significance of plain pottery traditions from both historically specific perspectives and from a comparative point of view; -examines the uses and functions of this pottery in relation to social negotiation and group identity formation; -helps scholars understand cross-regional similarities in development and use"..